2019
DOI: 10.1097/md.0000000000014785
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of erlotinib and celecoxib for patients with advanced non-small cell lung cancer

Abstract: This study evaluated the efficacy and toxicity of erlotinib and celecoxib (EC) for treating Chinese patients with advanced non-small cell lung cancer (ANSCLC) and epidermal growth factor receptor (EGFR) wild type.Totally, 75 subjects with ANSCLC and EGFR wild type were included. They all underwent EC treatment. The outcome measurements consisted of progression-free survival (PFS), overall survival (OS), complete response (CR), partial response (PR), stable disease (SD), progress disease (PD), and disease contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Besides, its tumoral response was associated with a low baseline MMP-9 and a decline in serum-soluble E-cadherin, tissue inhibitors of matrix metalloprotemase-1 (TIMP-1), and chemokine (C–C motif) ligand 15 (CCL15) . Additionally, a current retrospective study supported the efficacy and acceptable toxicity of this combination for treating patients with advanced non-small-cell lung cancer and EGFR wild type . Moreover, this combination inhibited growth and angiogenesis in non-small-cell lung cancer with EGFR exon 19 deletions through the modulation of the PI3K/AKT and ERK/Raf1-1 pathways .…”
Section: Cancer Prevention and Treatmentmentioning
confidence: 57%
See 1 more Smart Citation
“…Besides, its tumoral response was associated with a low baseline MMP-9 and a decline in serum-soluble E-cadherin, tissue inhibitors of matrix metalloprotemase-1 (TIMP-1), and chemokine (C–C motif) ligand 15 (CCL15) . Additionally, a current retrospective study supported the efficacy and acceptable toxicity of this combination for treating patients with advanced non-small-cell lung cancer and EGFR wild type . Moreover, this combination inhibited growth and angiogenesis in non-small-cell lung cancer with EGFR exon 19 deletions through the modulation of the PI3K/AKT and ERK/Raf1-1 pathways .…”
Section: Cancer Prevention and Treatmentmentioning
confidence: 57%
“…210 Additionally, a current retrospective study supported the efficacy and acceptable toxicity of this combination for treating patients with advanced non-smallcell lung cancer and EGFR wild type. 211 Moreover, this combination inhibited growth and angiogenesis in non-smallcell lung cancer with EGFR exon 19 deletions through the modulation of the PI3K/AKT and ERK/Raf1-1 pathways. 212 Interestingly, this combination treatment also enhanced radiosensitivity in human lung cancer cells.…”
Section: Clinical Studies Several Epidemiological and Clinicalmentioning
confidence: 99%
“…These findings suggested that CXB improved the antitumor effect of IR, benefited the prognosis, or reduced IR resistance in vivo. Evidence from other studies showed that CXB-erlotinib combination or CXB alone treatment can enhance radiosensitivity in A549 lung cells (40) and may be beneficial for patients with advanced NSCLC and EGFR wild type only (41). Apart from being used as a treatment of rheumatoid arthritis and osteoarthritis, CXB may hold promise of an antitumor treatment that requires further confirmation by clinical trials in the future.…”
Section: Discussionmentioning
confidence: 99%